Data privacy protection: A study on students awareness of personal data privacy protection in an E-health environment - Mohamed A.A.B.S.; Chen L.F. (American Scientific Publishers, 2023)
Investigating the underlying relationship between the existence of data protection framework in a country and its impact on e-health and how university students share and use personal information through an online medium. This research leads to the finding on the weakness that Malaysia PDPA 2010 have when it comes to the sharing of information in the electronic health sectors as well as the existence of the privacy paradox and its psychological influence on students when sharing personal information. Finding the weakness of PDPA 2010 in relation to the health industry would shed light on what is need to be done to remedy the problem. The analysis of the data from the research done on the students also measure students awareness of the scope of data protection law in their country and their motivation in sharing their personal information on the internet. Results of the study will then be used to discuss and suggest improvements that are needed in the current iteration of data privacy law in Malaysia. 2017 American Scientific Publishers All rights reserved.